Efektivitas Pengendalian Internal, Peran Audit Internal, Kompleksitas Instansi, dan Opini Audit Terhadap Kasus Korupsi - Utomo, Wahyu Setio; Hayat, Atma; Respati, Novita Weningtyas (Peneliti.net, 2025)
This research examines the effect of internal control effectiveness, the role of internal audit, the level of internal audit authority, internal audit size, ministry size, agency complexity and audit opinion on corruption in ministries/agencies in Indonesia.The effectiveness of internal control is seen from the number of internal control findings and non-compliance with statutory regulations in the BPK audit report, the role of internal auditors in an agency is proxied by the maturity of the SPIP in the BPKP report, the level of internal audit authority in the form of an internal audit organizational structure at the same level echelon I and II, internal audit size is seen from the number of BPKP internal audits, ministry size is proxied from the realization of the expenditure budget (in percentage), agency complexity is proxied by the number of work units, and audit opinion is taken from the BPK audit report. The dependent variable is corruption in ministries/agencies seen from the number of corruption cases in the KPK report with inchract status in 2018-2022. This research uses secondary data with a sample of 405 ministries/agencies in Indonesia, the analysis method used is binary logistic regression. The research results show that the role of internal audit reduces corruption cases. However, the realization of the expenditure budget (in percentage) positively affects the increase in corruption cases. Meanwhile, the effectiveness of internal control, level of audit authority, number of internal auditors, number of work units and audit opinions in ministries/agencies do not affect corruption.